Projection on pavement life time for FR 222 access road to Gambang toll - Amrina, Abu Bakar (2012)
Flexible pavements in Malaysia are designed until 1.0 to 15 years design life to support load from the vehicles. Sometimes these roads are not able to carry the load with the specified design life. The proposed study area that is looking at is FR 222 access road to Gambang Toll. From the observation, the condition of pavement of FR 222 (access road to Gambang Toll & UMP) is sub-standard. It is because the road was gazette as industrial. access prior to the opening, of Garnbang Toil Plaza and UMP and these resulted in uneven pavement surface that inconvenient to road users. The objectives of this study are to estimate the thickness of pavement on FR 222 access road to Gambang Toll using Arahan Teknik (Jalan) 5185, Manual on Pavement Design, Jabatan Kerja Raya and to formulate pavement lifetime 'based on failure analysis of flexible pavement. Traffic volume count, interview survey and visual inspection are conducted on this study to accomplish and achieved the study objectives.